Tá Falando: processo de criação da iluminação cênica do espetáculo “Barrela” - SILVA, Paula Nayara dos Santos (2018)
This study aimed to describe the process of creating a stage lighting experiment, which used and produced alternative materials for theatrical presentation in unconventional spaces. The central axis is the story of the creation process with the construction of alternative lighting materials for the show "lye". During the thesis, I present the process in stages, from the first meeting with the group, the type of material used, the failed attempts in the search for hit and the maturing of the work. The research found regarding guided in the assembly of the show "lye", authored by Plinio Marcos and group staging "The Varisteiros". With the purpose to discuss and point out ways for stage lighting as a teaching and learning tool.